Rancang Bangun Sistem Monitoring Kateter Pasien Berbasis Iot (Sismoniterin) Pada Rumah Sakit Mitra Medika Medan - Wiwin Sry Adinda Banjarnahor (Cattleya Darmaya Fortuna, 2022)
The IoT-based catheter monitoring system (Sismoniterin) is a system created to assist health workers, especially nurses and the patient's family, in monitoring the height of the contents (volume) of the catheter so that there is no leakage in the patient's urinary catheter due to excess storage capacity. This system uses a water level sensor to detect the urine level on the patient's catheter and the NodeMCU ESP 8266 as a microcontroller that will help the sensor to send data, namely the patient's urine on the catheter via the internet, and can also apply the IoT concept which can monitor the patient's catheter automatically. The results of this study are in the form of a system that can send notifications via whatsapp nurses regarding the volume of the patient's catheter. Besides being equipped with quite a lot of output, this system uses a rechargeable lithium battery. However, the drawback of this system is that this system is not equipped with an LCD to see the remaining battery working on the system so that the nurse must prepare a backup battery if the battery system is being recharged, so they can use a spare battery to be able to operate the system...